1967
DOI: 10.1099/00221287-47-2-207
|View full text |Cite
|
Sign up to set email alerts
|

On the Taxonomic Status of 'Quin's Oval' Organisms

Abstract: SUMMARYPurified suspensions of the sheep rumen organism known colloquially as ' Quin's oval' were prepared from sheep rumen liquor. The chemical composition of cell walls prepared from the organisms of these suspensions was found to include protein, lipid and polysaccharide. A fraction from these walls, obtained after removal of much of the protein and polysaccharide, was shown to contain muramic acid, glucosamine and diaminopimelic acid. These findings are consistent with this organism being regarded as a Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The 16s rRNA sequence of QO is related to those of the gram-positive group, even though QO has a gram-negative ultrastructure (23). Similar relatedness within the grampositive groups has been found in the sequences of other gram-negative bacteria, such as those in the genera Selenornonas, Megasphaera, and Sporomusa, to which the sequence of QO is most closely related.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…The 16s rRNA sequence of QO is related to those of the gram-positive group, even though QO has a gram-negative ultrastructure (23). Similar relatedness within the grampositive groups has been found in the sequences of other gram-negative bacteria, such as those in the genera Selenornonas, Megasphaera, and Sporomusa, to which the sequence of QO is most closely related.…”
Section: Resultsmentioning
confidence: 55%
“…It includes nonsporing, heterotropic, mesophilic, anaerobic ovals with tumbling motilities and linear tufts of flagella on one side of their cells (14). The genus is gram negative, and its cell wall contains a distinct outer membrane and muramic and m-diaminopimelic acids (23). It reproduces by binary fission, and it usually occurs as singles and pairs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…He named the organism Schizosaccharomyces ovis in the belief that it was a yeast, but subsequent workers concluded that this was not so (Ingram & McGaughey, 1948;van der Westhuizen, Oxford & Quin, 1950;Oxford, 1955) on the grounds that the organism would not grow in conventional yeast media, was motile and Gram-negative. Positive evidence for its status as a bacterium was supplied by Wicken & Howard (1967) who identified 2,4-diaminopimelate and rnuramate in cell wall preparations of Q.O. Q.O.…”
Section: Introductionmentioning
confidence: 99%